Juventude Espírita Irmão Bosco e a produção de saberes na experiência da evangelização infanto-juvenil no Grande Bom Jardim - Rodrigues, Lúcia Vanda (2012)
This dissertation is the result of a research Master’s Program in Graduate Education in Brazilian Federal University of Ceará – UFC. Aimed to uncover the knowledge built on the experience of a group of young spirit in their practices of evangelism/education of children and adolescents and the meaning of this experience for these young people surveyed. Aim of carrying out this research; contribute to studies on the production and legitimation of knowledge in other areas beyond the school, covering new dimensions that constitute the human being, as the case of spirituality in the education aspect of the Spirit through the Spirit. The study was conducted in the home of Francisco Spirit Center, located in the Greater Good of the Community Garden, with the five components of the Bosco Youth kindred spirit, one boy e four girls, aged between 22 and 29 years. In collecting data, we used a qualitative approach, through dialogues and the interviews, press conferences, field diary and participant observation. The research pointed out some knowledge constructed by the research subjects in the experiment they experience: Need knowledge of the lives of students participate in the education of Children and Youth Home of Francis, so that the spirit educational meetings are focused according to the reality in which are inserted, greater promotion of dialogue between educators and the students, so that the subjects of the educational process can have a better knowledge of each other and reflect on themselves in the reality that mediates, the introduction of play in children’s educational process, in order to teach a playful and enjoyable, stimulation thinking and imagination of children, allowing them to explore different types of behaviors, situations, capabilities and limitations. “Learning”, “education with love” and “transformation”, some of the meanings of the young people who experience the experience as educators spirits. To develop this study was necessary to use the thought of authors such as theoretical contributions to a better understanding of the subjects studied, among which I quote Melucci (1997), Pais (1996), Matos (2003, 2007), Kardec (1995, 1998, 2005, 2007 and 2008), Pires (1995), Linhares (2005), Charlot (2000) and Freire (1978) among others that are cited throughout this work, which were the sources of the theoretical underpinnings of this study.